Evaluasi Proses Bisnis Administrasi Pelayanan Akademik Semester Antara pada Fakultas Ilmu Komputer Universitas Brawijaya (FILKOM UB) dengan Metode Quality Evaluation Framework (QEF) - Nisriinaa 'Aaliyah; Intan Sartika Eris Maghfiroh; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Intermediate Semester Activities (SA) are regular lecture activities packaged in the form of short semesters. There is a website developed by the Faculty of Computer Science, Brawijaya University (FILKOM UB) to help students administer the Intermediate Semester called FILKOM Apps. However, not all that student needs can be met because they still require consideration from the organizers. Delineation of the flow of administration in this activity requires analysis and modeling of business processes. There are five business processes identified and modeled using BPMN. The results of evaluating business processes using the QEF method identified 34 quality factors and among them there are 15 quality factors which do not meet the target because it has a gap in the calculation. Then do a root cause analysis using the Fishbone Diagram method identifies the top three categories that cause problems, namely categories measurement, man power and method. Business process improvement recommendations include a comparison of currently used business process simulations (as-is) with the recommended business process (to-be) using measurement time analysis on the Bizagi Modeler application. The design of SA has an increase in time efficiency of 26.04%. The SA data collection has an increase in time efficiency of 37.8%. In SA scheduling, it has an increase in time efficiency of 15.58%. SA registration and payment has an increase in time efficiency of 2.49%. The SA validation has an increase in time efficiency of 7.47%.